Co-Payments and Inequality in Gingival Bleeding and Dental Visits - Noriko Nakazawa; Taro Kusama; Kenji Takeuchi; Sakura Kiuchi; Tatsuo Yamamoto; Katsunori Kondo; Ken Osaka; Jun Aida (International Dental Journal, 2023)
ABSTRACT: Objectives: Japan's universal health insurance covers a wide range of dental treatments, and the co-payment rates differ by age. We investigated whether the inequality in gingival bleeding and dental visits was smaller amongst those with lower co-payment rates. Methods: This cross-sectional study used data from the 2019 Japan Gerontological Evaluation Study. The participants were functionally independent adults aged 65 years or older. The dependent variables were current gingival bleeding as a symptom of periodontal diseases and dental nonattendance for treatment in the past year. The independent variables were ridit scores of equivalent income and educational status. For covariates, we used age, sex, and the number of remaining teeth. To evaluate the inequalities, we used the slope index of inequality (SII) and the relative index of inequality (RII). We also conducted stratified analyses by co-payment rates (30%, 20%, and 10%) to clarify the difference in inequalities by co-payment rate. Results: A total of 15,389 participants were included in the analysis; their mean age was 71.8 (SD = 4.1) and 51.8% were women. There were significant absolute and relative inequalities in gingival bleeding and dental visits by equivalent income and education. With regards to educational status, inequalities were lower with a decrease in the co-payment rate. In particular, relative inequality by education in gingival bleeding was the largest amongst the 30% co-payment group (RII, 1.918; 95% confidence interval [CI], 1.386 to 2.656). For gingival bleeding, the absolute and relative inequality by equivalent income were not significant amongst the 10% co-payment group (SII, −0.003; 95% CI, −0.003 to 0.028; RII, 1.006; 95% CI = 0.676 to 1.498). Conclusions: A low co-payment rate was associated with smaller inequalities in gingival bleeding and dental visits by equivalent income and educational status.